Alcohol-Induced Glycolytic Shift in Alveolar Macrophages Is Mediated by Hypoxia-Inducible Factor-1 Alpha - Morris, Niya L.; Michael, David N.; Crotty, Kathryn M.; Chang, Sarah S.; Yeligar, Samantha M. (Frontiers in Immunology, 2022)
Excessive alcohol use increases the risk of developing respiratory infections partially due to impaired alveolar macrophage (AM) phagocytic capacity. Previously, we showed that chronic ethanol (EtOH) exposure led to mitochondrial derangements and diminished oxidative phosphorylation in AM. Since oxidative phosphorylation is needed to meet the energy demands of phagocytosis, EtOH mediated decreases in oxidative phosphorylation likely contribute to impaired AM phagocytosis. Treatment with the peroxisome proliferator-activated receptor gamma (PPARγ) ligand, pioglitazone (PIO), improved EtOH-mediated decreases in oxidative phosphorylation. In other models, hypoxia-inducible factor-1 alpha (HIF-1α) has been shown to mediate the switch from oxidative phosphorylation to glycolysis; however, the role of HIF-1α in chronic EtOH mediated derangements in AM has not been explored. We hypothesize that AM undergo a metabolic shift from oxidative phosphorylation to a glycolytic phenotype in response to chronic EtOH exposure. Further, we speculate that HIF-1α is a critical mediator of this metabolic switch. To test these hypotheses, primary mouse AM (mAM) were isolated from a mouse model of chronic EtOH consumption and a mouse AM cell line (MH-S) were exposed to EtOH in vitro. Expression of HIF-1α, glucose transporters (Glut1 and 4), and components of the glycolytic pathway (Pfkfb3 and PKM2), were measured by qRT-PCR and western blot. Lactate levels (lactate assay), cell energy phenotype (extracellular flux analyzer), glycolysis stress tests (extracellular flux analyzer), and phagocytic function (fluorescent microscopy) were conducted. EtOH exposure increased expression of HIF-1α, Glut1, Glut4, Pfkfb3, and PKM2 and shifted AM to a glycolytic phenotype. Pharmacological stabilization of HIF-1α via cobalt chloride treatment in vitro mimicked EtOH-induced AM derangements (increased glycolysis and diminished phagocytic capacity). Further, PIO treatment diminished HIF-1α levels following EtOH exposure. These studies support a critical role for HIF-1α in mediating the glycolytic shift in energy metabolism of AM during excessive alcohol use.